2009
DOI: 10.1111/j.1574-6968.2009.01683.x
|View full text |Cite
|
Sign up to set email alerts
|

The site-specific recombination system of actinophage TG1

Abstract: Actinophage TG1 forms stable lysogens by integrating at a unique site on chromosomes of Streptomyces strains. The phage (attP(TG1)) and bacterial (attB(TG1)) attachment sites for TG1 were deduced from comparative genomic studies on the TG1-lysogen and nonlysogen of Streptomyces avermitilis. The attB(TG1) was located within the 46-bp region in the dapC gene (SAV4517) encoding the putative N-succinyldiaminopimelate aminotransferase. TG1-lysogens of S. avermitilis, however, did not demand either lysine or diamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…We have previously demonstrated that the integrase system of actinophage TG1 works eYciently not only in homologous Streptomyces cells, but also in heterologous E. coli cells (Morita et al 2009). This indicates that integrase expressed from the int TG1 gene in E. coli cells catalyzes a site-speciWc recombination between attB and attP sites of TG1 phage without detrimental eVects on the host bacteria.…”
Section: Over-production and Puriwcation Of Tg1 Integrasementioning
confidence: 98%
See 2 more Smart Citations
“…We have previously demonstrated that the integrase system of actinophage TG1 works eYciently not only in homologous Streptomyces cells, but also in heterologous E. coli cells (Morita et al 2009). This indicates that integrase expressed from the int TG1 gene in E. coli cells catalyzes a site-speciWc recombination between attB and attP sites of TG1 phage without detrimental eVects on the host bacteria.…”
Section: Over-production and Puriwcation Of Tg1 Integrasementioning
confidence: 98%
“…In a previous paper we have established an in vivo integration system based on actinohage TG1 and relevant attachment sites (Morita et al 2009). Although integrases of TG1 and C31 share a high sequence similarity, especially at the N-terminal catalytic domain, attachment sites (attP, attB) of two integrases were distinct and not interconvertible (Ikeda et al 2003;Morita et al 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…pGSBC1 and pTYM1-GSBC contain the entire goadsporin biosynthetic gene cluster and actinomycete genome integration modules that consist of integration genes isolated from actinophages phiC31 14) and TG1. 15) Each integrase recognizes a different attB site in a genome, enabling the two plasmids to integrate into a single genome. After transconjugation, site-specific integrases phiC31 and TG1 catalyze unidirectional recombination between the vector attP and the chromosomal attB, and single integrated recombination occurs at the attB site.…”
Section: Construction Of Recombinant Strains Containing Two or Three mentioning
confidence: 99%
“…The alternatives to the ΦC31 integrative site in Streptomyces are the ΦBT1 (Gregory et al 2003), TG1 (Morita et al 2009) and SV1 (Fayed et al 2014) integrative sites. The ΦBT1 derived vectors integrate into the attP site localized into the SCO4848 gene (S. coelicolor genome) (Gregory et al 2003), while the TG1 plasmids integrate at SCO3658 (Fayed et al 2014) and SV1 plasmids at SCO4383 (Fayed et al 2014).…”
Section: Introductionmentioning
confidence: 99%